Me. Rev. Stat. tit. 2, ch. 26, § 24 (1871) - (:unkn) unknown (My University, 1871)
Allowed municipal officers to regulate storage or transportation of gun powder. Also allowed municipal officers to enter any building with a search warrant to find concealed articles contrary to regulations..
Keywords: GUNPOWDER - STORAGE